Secret key cryptography : ciphers, from simple to unbreakable - Rubin, Frank (Cryptographer) (Manning Publications, 2022)
Explore the fascinating and rich world of Secret Key cryptography! This book provides practical methods for encrypting messages, an interesting and entertaining historical perspective, and an incredible collection of ciphers and codes—including 30 unbreakable methods.